The clinical diagnosis of pelvic inflammatory disease - reuse of electronic medical record data from 189 patients visiting a Swedish university hospital emergency department - van Vuuren Caroline; Sundquist Kristina; Eggert Jan; Fianu-Jonasson Aino (BMC, 2006)
Abstract Background The pelvic inflammatory disease (PID) diagnosis is mostly based on clinical findings. However, few studies have examined the clinical basis for the diagnostics of PID, which was the aim of this study. Methods A retrospective study was performed of 189 out-patients diagnosed as having PID at the obstetric and gynecological emergency department of a Swedish university hospital. Data on symptoms, signs, pelvic examination and laboratory tests were extracted from the electronic medical records in comparison with the diagnostic criteria of the PID Guideline of the US Center of Disease Control from 2002 (CDC 2002 Guidelines). Results Eight symptoms in varying combinations were associated with the PID diagnosis. Most of them are mentioned in the CDC 2002 Guidelines. Detected rates of C. Trachomatis (CT) and N. Gonorrhoeae (NG) were 5% and 0%, respectively, among the tested patients (CT = 52% and NG = 12%). The C-reactive protein was normal in the majority of tested patients. Conclusion The clinical basis for the diagnostics of PID was largely in accordance with the criteria in the CDC 2002 Guidelines. The limited number of CT tests performed is somewhat disappointing, considering the fact that effective disease prevention includes widespread CT screening. Further studies in different settings are needed in order to analyze how the testing rate for CT can be improved in clinical praxis.